The influence of social capital on self-rated health and depression - The Nord-Trøndelag health study (HUNT) - Erik R. Sund; Stig H. Jørgensen; Andy Jones; Steinar Krokstad; Marit Heggdal (Norsk Forening for Epidemiologi, 2007)
The article examines the relationship between neighbourhood social capital and two health outcomes: selfrated health and depression. A total of 42,571 individuals aged 30-67 years participated in a cross-sectional total population health study in Nord-Trøndelag in 1995-1997 (HUNT II) and were investigated using multilevel modelling. Aims were, first, to investigate potential area effects after accounting for the characteristics of individuals in the neighbourhoods (N = 155), and, second, to explore the relationships between contextual social capital (the level of trust at the neighbourhood level and the level of local organizational activity) and the two health measures. Models with stepwise inclusion of individual level factors attenuated the ward level variance for both self-rated health (PCV: 41%) and depression (PCV: 43%). The inclusion of the two contextual social capital items attenuated the ward level variance for both self-rated health and depression, however to varying degrees. At the individual level, contextual social capital was associated with both self-rated health and depression. Individuals living in wards with a low level of trust experienced an increased risk of 1.36 (95% CI: 1.13-1.63) for poor self-rated health compared to individuals in wards with a high level of trust. For depression, this effect was even stronger (OR 1.52, 1.23-1.87). The associations with the level of organizational activity were inconsistent and weaker for both health outcomes. It was concluded that geographical variations in self-rated health and depression are largely due to the socioeconomic characteristics of individuals. Nevertheless, contextual social capital, expressed as the level of trust, was found to be associated with depression and self-rated health at individual level.